Monitoring the agri-food system in Myanmar: Mechanization service providers – July 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Mechanization service providers (MSPs) in Myanmar were originally interviewed by telephone in summer 2020, fall 2020, and June 2021, covering mostly combine-harvester service providers (CHSPs) and tractor service providers (TSPs), to determine how their businesses were being affected by COVID-19 related restrictions and political instability. The results of those surveys were published in Myanmar Strategy Support Program Notes 07, 12, 17, 39, 43 and 59 respectively. To trace the continuing impact of the COVID-19 pandemic as well as the current political and social conditions on their economic activities, a seventh phone survey of MSPs was conducted in late July 2021. This reports on the results of the seventh survey as well as on some trends from earlier surveys.